1985
DOI: 10.1038/317729a0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of factor VIII procoagulant antigen in human liver hepatocytes

Abstract: Factor VIII is generally believed to circulate in blood as a multimeric complex of two glycoproteins which are physiologically and immunologically distinct. One component of the factor VIII complex is factor VIII procoagulant activity (FVIII:C) which is associated with factor VIII/procoagulant antigen (FVIII:Ag, formerly FVIII/CAg). The second, larger unit of the complex is factor VIII/von Willebrand factor (vWF:Ag, formerly factor VIII-related antigen or FVIIIRAg). FVIII:C has anti-haemophilic activity and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 11 publications
3
52
0
Order By: Relevance
“…The data represent the mean and standard deviation from cultures obtained from three separate preparations. (12). In contrast, fVIII was localized immunohistologically to LSECs but not hepatocytes (9,10,25,26).…”
Section: Fig 4 Quantitation Of Fviii From Cultured Lsecsmentioning
confidence: 85%
“…The data represent the mean and standard deviation from cultures obtained from three separate preparations. (12). In contrast, fVIII was localized immunohistologically to LSECs but not hepatocytes (9,10,25,26).…”
Section: Fig 4 Quantitation Of Fviii From Cultured Lsecsmentioning
confidence: 85%
“…Early studies suggested that FVIII was expressed mostly in hepatocytes, 40 but other studies found that FVIII was expressed in LSEC and macrophages as well, whereas virtually no signal for FVIII was detected in hepatocytes. 20,41 More recently, we and others established that FVIII is largely produced and secreted by LSEC.…”
Section: Discussionmentioning
confidence: 99%
“…The liver has been implicated as a major site of F.VIII synthesis due to the ability of liver transplantation to cure hemophilia A in canine models as well as human patients (232)(233)(234). A number of studies have reported the presence of F.VIII mRNA and protein in hepatocytes in vivo, F.VIII production by hepatocytes cultured in vitro, and even the ability to restore clotting activity through hepatocyte transplantation (235)(236)(237)(238)(239). Conversely, others have reported F.VIII synthesis in liver sinusoidal epithelial cells (LSECs) but not hepatocytes, or even in both cell types (240)(241)(242)(243)(244)(245)(246).…”
Section: Additional Challenges In Hemophilia Amentioning
confidence: 99%